Management of Hypertension in CAKUT: Protective Factor for CKD - Gabriele, Marina M.; Koch Nogueira, Paulo C. (Frontiers in Pediatrics, 2019)
Patients with congenital kidney and urinary tract abnormalities (CAKUT) will often develop end-stage renal disease at some point and the need for renal replacement therapy is associated with high rates of morbidity and mortality. Hence, efforts to slow the progression of the disease are essential. Hypertension has been proven to be an independent risk factor for faster decline of glomerular filtration rate in renal patients, but studies involving only children with CAKUT are scarce. We performed a literature review to explore the association of hypertension with faster chronic kidney disease progression in children with CAKUT and also treatment options in this condition. A recent study reported an annual decline in GFR of 1.8 ml/min/1.73m2 among hypertensive patients with non-glomerular CKD, compared with 0.8 ml/min/1.73m2 in normotensive children. A multicenter prospective cohort in Brazil showed that a 1-unit increase in systolic blood pressure Z-score was associated with a 1.5-fold higher risk of disease progression. Since renin-angiotensin-aldosterone system activation is the most important mechanism of hypertension in these children, the first-line therapy involves the use of inhibitors of this axis, including angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers type I, which also promote an anti-fibrotic effect. Recent studies have shown a good safety profile for use in patients with chronic kidney disease and also in those with solitary kidneys. Hypertension is an independent risk factor for kidney disease progression and should be promptly managed for renal protection, especially among patients with CAKUT, the primary cause of chronic kidney disease in the pediatric population.